Correction of simple congenital heart defects by right axillary thoracotomy in adults. Issue 11 (2nd September 2019) - Yang, Ming; Su, Junwu; Liu, Aijun; Fan, Xiangming; Li, Gang; Li, Bin; Liu, Yinglong
Abstract: Background: Right axillary thoracotomy has been performed for open‐heart procedures as a more aesthetic alternative to standard median sternotomy. This study aimed to evaluate the efficacy and safety of right axillary thoracotomy for the correction of simple congenital heart defects in adults. Methods: Between January 2014 and December 2017, the clinical data of 180 adults who underwent right axillary thoracotomy for simple congenital heart defects were compared with the data of a paired group of 192 adults who underwent median sternotomy. Results: Compared with the median sternotomy group, the right thoracotomy group showed shorter operative time, postoperative mechanical ventilation time, and postoperative hospitalization duration, as well as less drainage and transfusion volumes ( P  < .05). Aortic cross‐clamping time, cardiopulmonary bypass time, and length of intensive care unit stay were similar between groups. No mortality or significant residual defects were reported in either group during follow‐up. In total, 172 patients (95.6%) in the right thoracotomy group and 134 patients (69.8%) in the median sternotomy group were satisfied with their cosmetic results ( P  < .01). Conclusions: A right axillary thoracotomy is as safe and effective as a median sternotomy for the correction of simple congenital heart defects in adults. With lower trauma and better cosmetic results, this procedure provides a good alternative to the standard median sternotomy.